Histological and Histometrical Studies on Ductus Deferens of Guinea Fowl (Numida meleagris) - Tamilselvan, S. (Indian Journal of Veterinary Anatomy, 2020)
The present study carried out on ductus deferens of 54 apparently healthy male guinea fowl (Pearl variety) at different age groups from day old, 2, 4, 8, 12, 16, 20, 24 and 28 weeks at monthly intervals. The ductus deferenswas paired extended from caudal end of epididymis to opening of urodeum. The ductus deferens was tubular organ, which lined by epithelial layer and thick fibromuscular layer. The ductus deferens of guinea fowl consisted of an epithelial layer and fibromuscular layer. The epithelial layer of ductus deferens was lined by pseudostratified columnar epithelium non-ciliated in all the age groups studied. The wall of the ductus deferens was made up of loose connective tissue. Its luminal surface had few longitudinal mucosal folds and the lumen tightly packed with spermatozoa.